Case report: Peripheral nerve stimulation relieves post-traumatic trigeminal neuropathic pain and secondary hemifacial dystonia - Li, Junchi; Li, Yongjie; Shu, Wei (Frontiers in Neurology, 2023)
Post-traumatic trigeminal neuropathic pain (PTNP) combined with secondary dystonia are rare sequelae of orofacial injury and often do not respond to conservative treatment. The consensus on treatment for both symptoms is yet to be standardized. This study reports the case of a 57-year-old male patient with left orbital trauma who developed PTNP immediately after the injury and secondary hemifacial dystonia 7 months thereafter. To treat his neuropathic pain, we performed peripheral nerve stimulation (PNS) using a percutaneously implanted electrode to the ipsilateral supraorbital notch along the brow arch, which instantly resolved the patient's pain and dystonia. PTNP was relieved in a satisfactory manner until 18 months after the surgery, despite a gradual recurrence of the dystonia since 6 months after the surgery. To the best of our knowledge, this is the first reported case of PNS used for the treatment of PTNP combined with dystonia. This case report highlights the potential benefits of PNS in relieving neuropathic pain and dystonia and discusses the underlying therapeutic mechanism. Moreover, this study suggests that secondary dystonia occurs due to the uncoordinated integration of afferent sensory and efferent motor information. The findings of the present study indicate that PNS should be considered for patients with PTNP following the failure of conservative treatment. Secondary hemifacial dystonia may benefit from PNS upon further research and long-term assessment.